2007
DOI: 10.1002/j.2050-0416.2007.tb00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Hydrophobins in the Barley-to-Beer Chain

Abstract: Fungal hydrophobins have been shown to induce gushing of beer. In order to study the occurrence and fate of hydrophobins at different stages of the production chain of beer, barley samples artificially infected in the field with Fusarium culmorum, F. graminearum and F. poae were collected during the growing period as well as during various stages of the malting process. In addition, naturally infected malt was brewed in pilot scale and samples were collected throughout the process. The samples were assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 12 publications
(26 reference statements)
1
44
1
2
Order By: Relevance
“…By nature, they are thermostable and Műller et al [103] reported that 10% of hydrophobins go through the processes and temperatures applied during brewing process unchanged, transfer to beer and can cause gushing. A similar claim was made by Sarlin et al [79]. Kleemola et al [92] and Sarlin et al [80] demonstrated that the addition of purified fungal hydrophobins to beer causes gushing.…”
Section: Gushing-an Important Economic Factorsupporting
confidence: 68%
See 3 more Smart Citations
“…By nature, they are thermostable and Műller et al [103] reported that 10% of hydrophobins go through the processes and temperatures applied during brewing process unchanged, transfer to beer and can cause gushing. A similar claim was made by Sarlin et al [79]. Kleemola et al [92] and Sarlin et al [80] demonstrated that the addition of purified fungal hydrophobins to beer causes gushing.…”
Section: Gushing-an Important Economic Factorsupporting
confidence: 68%
“…Fusarium species are known producers of mycotoxins, but they also excrete hyrophobins that cause gushing [35,[76][77][78][79][80][81]. Gushing can be described as uncontrolled, eruptive foaming of beer after a bottle has been opened, without previous shaking or any agitation (Figure 4).…”
Section: Gushing-an Important Economic Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Cox et al (2009) reported that 0.1 wt% HFBII forms exceptional stable foams across a wide range of solution pH conditions in simple solutions. However their presence in beer is undesirable because they are responsible for gushing (Sarlin et al, , 2007. Gushing is the spontaneous and wild overfoaming of overcarbonated beverages that occurs at the opening of the container without any shaking.…”
Section: Introductionmentioning
confidence: 99%